Narratives and place experience(s): basis for a landscape museum - Abreu, João (2018)
Landscape is a heritage that concerns everyone. Economic development, efficient sustainability and an inclusive social and territorial growth require a cultural transformation based on knowledge, innovation and a reinforced articulation of synergies. The project proposes the creation of a culturally mediated digital platform between landscape and the people of a specific territory. The project is practice-oriented, flexible, open and "alive" in its very essence as it results from the interaction over time of natural and human factors that shape our landscape.